Vocal breathing technique of 'Non So Piu Cosa Son, Cosa Faccio' by Isabel Leonard / Nur Natasha Husaini - Husaini, Nur Natasha (2023)
This research aims to investigate the voice projection of Isabel Leonard in Non So Piu Cosa Son, Cosa Faccio by Wolfgang Amadeus Mozart. The purpose of this research as a contribution to singer comprehension is to emphasise the importance of developing voice breathing technique functions in singing that are required to be understood in a proper way of use. The objectives of this research study are to investigate the types of breathing technique used by Isabel Leonard in Non So Piu Cosa Son, Cosa Faccio and to identify the problems with breathing technique faced by the singers while singing a classical piece.